Metalinguistic abilities: The contribution to writing - Irini K. Zerva (Social Sciences and Humanities Open, 2023)
The purpose of this study was to explore the contribution of metalinguistic abilities to learning procedures and specifically to writing, according to the beliefs of teachers in primary schools and their students, after the application of a pilot teaching program, which focuses on the enhancement of metalinguistic abilities and metalinguistic writing techniques and on the reinforcement of metalinguistic abilities and metalinguistic writing techniques. Data analysis showed that both teachers and students believe that metalinguistic abilities contribute positively to students' language performance and more specifically to writing, they make students more confident and satisfied with their language use and writing products and for this reason students prefer teaching methods, which aim at developing metalinguistic abilities and reinforcing metalinguistic skills. This research was based on the acknowledgement of the fact that students demonstrate weakness in the correct use of their mother language and do not achieve high quality written products. Metalinguistic abilities are factors of awareness and purposeful use of the language. Questions have, therefore, occurred about the contribution of metalinguistic abilities to students' language improvement and the deeper acquisition and better use of the mother tongue. Review of the relevant bibliography has revealed an extensive use of fragmentary techniques and language teaching methods, as far as not only mother tongue but also foreign languages are concerned, without however the contribution of a specific teaching program focused on the development and cultivation of metalinguistic abilities, something that the present research has attempted. A pilot teaching program was applied aimed specifically at teaching and developing writing strategies based on accenting and exploiting students' metalinguistic abilities. There have been data collections before and after the application of the pilot teaching program, from the research sample and the monitoring team at least twice. Data analysis confirmed the positive contribution of metalinguistic abilities to language performance, to students' ability to predict and avoid or eventually correct their errors and to developing students' confident production of written language. Finally, the interaction between all these factors and the quality of the language product has also been confirmed. In conclusion, metalinguistic abilities are an important regulative factor, which influences language performance, especially in writing and their contribution to the better learning and more effective use of the students’ mother tongue, even ay primary education level, has been acknowledged by both teachers and their students.